Can resource policy adjustments effectively curb regional "resource curse" ? new evidences from the "energy golden triangle area" of China. (October 2021) - Xu, Xiaoliang; Xu, Xuefen
Abstract: When resource endowment supports regional economic growth, it also induces regional "resource curse". However, few studies have fully considered the impact of resource policy adjustments on avoiding the "resource curse" in energy concentration area. In this paper, we appraise the impacts on regional "resource curse" in the "Energy Golden Triangle area" of China by resource policy adjustment by an improved dynamic CGE model with cleaning sector and non-cleaning sector. Meanwhile, coal resource tax reform is adopted to be as a representative resource and environment policy adjustment. The results show that: 1) coal resource tax reform has a significant inhibitory effect in the total outputs. 2) coal resource tax reform has a positive influence on GDP and crowds out energy resources from the non-clean sector to clean sector. 3) Local taxation in the "Energy Golden Triangle area" of China has increased greatly by reform.4) Coal resource tax reform has curbed the regional "resource curse" in the "Energy Golden Triangle area" of China to a certain extent, but a huge regional difference exists. 5) Coal resource tax reform can effectively suppress energy consumption and reduce emissions of major pollutants in the "Energy Golden Triangle area" of China. Highlights: Coal resource tax reform has a significant inhibitory effect in the total outputs. The reform has a positive influence on GDP rises rapidly by energy sector boom. Local taxation in the "Energy Golden Triangle area" has increased greatly. The reform has curbed the regional "resource curse" in the "Energy Golden Triangle area". The reform can effectively suppress energy consumption and reduce emissions of major pollutants.